Pacemaker need after sutureless aortic valve replacement: the role of the learning curve. Issue 2 (February 2021) - Mikus, Elisa; Calvi, Simone; Tavazzi, Luigi; Brega, Carlotta; Tripodi, Alberto; Pin, Maurizio; Manfrini, Marco; Zucchetta, Fabio; Tenti, Elena; Albertini, Alberto
Abstract : Aim: Aortic valve replacement (AVR) using sutureless prosthesis is a reasonable alternative in those patients with aortic stenosis who would benefit from reduced cross clamp time, such as elderly and high-risk patients. Actually, excellent performances have been demonstrated in hemodynamic outcomes and safety, but some questions remain open regarding long-term durability and the need for postoperative pacemaker implantation. Methods: Between January 2014 and August 2019, all 436 patients [male 40.6%, median age 78 years interquartile range (73–82)] treated with sutureless AVR with a Perceval prosthesis were included in our analysis. Results: The univariate logistic regression showed previous aortic valve surgery [ P  = 0.028; odds ratio (OR) 3.248], dialysis ( P  = 0.036; OR 6.435), renal insufficiency ( P  = 0.021; OR 2.75), EuroSCORE II ( P  = 0.016; OR 1.051) and year of operation ( P  < 0.01; OR 0.658) as factors associated with the development of atrioventricular type II or type III block or junctional block requiring pacemaker implantation. The overall incidence of pacemaker implantation after sutureless AVR was 7.1% in the current study, but it dropped to 3.8 and 4.7%, respectively, in 2018 and 2019. Conclusion: The Perceval aortic valve is associated with encouraging postoperative results. The incidence of pacemaker implantation is strictly linked to the surgeons' experience, decreasing year by year after an adequate sizing, reaching a percentage comparable with sutured valve. Abstract : Supplemental Digital Content is available in the text